Analisis Kondisi Sumber Daya Mineral Brown Canyon Semarang - Dewi, Clara Angelina Kusuma; Purwandari, Alberta Kristi; Maharani, Desi Febrina; Divina, Maria Beneficia; Ismail, Amrizarois (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2023)
Natural resources (SDA) are wealth that not every country in the world has. Natural Resources are divided into several parts according to their classification, including Mineral Resources. Mineral Resources are natural resources that contain minerals and mining materials that have economic value. The materials contained therein are usually used as high-value production materials, this is what causes mineral resources to sometimes be used inefficiently. One of the mineral resources in Indonesia is in Central Java Province, precisely in the city of Semarang, which is commonly known as "Brown Canyon". The "Brown Canyon" area is rich in natural mineral resources which are ultimately used by the community as work land in the form of mining, on the other hand, "Brown Canyon" is also used as a natural tourist attraction. The mineral content in the form of sand and stone in this area has a promising economic value for the surrounding community, but behind this economic value the existing content or reserves are not yet fully known. In this research the author will analyze the current conditions of the "Brown Canyon" area, especially in terms of the availability of mineral resources in the area using qualitative and survey methods. The results of the calculation of mineral reserves were obtained at 1,918,800 tons. Mineral reserves in the form of stone and sand in Brown Canyon will be exhausted within 17 years with annual mineral resource extraction of 108,000 tons.